The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/s1516-8913201500076
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Anticancer Activity of Grape Seed Extract on Skin Cancer Cell Lines A431

Abstract: In this study, grape seeds were extracted using ethyl acetate and petroleum ether by solvent-solvent extraction method. The phytochemical tests were performed to identify different phytochemical compounds present in the grape seed extract (GSE). Antibacterial activity of the GSE was determined using agar diffusion method against Grampositive and Gram-negative bacteria. Gas chromatography-mass spectrometry (GC-MS) and Fourier transform infrared spectroscopy (FTIR) analysis was done to identify the presence of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 10 publications
3
13
0
Order By: Relevance
“…Si–O stretching bend of methylene group (–CH 2 ) was also observed at peak 721.93 cm ‒1 . The spectra pattern was similar with Moringaceae seed oil (Bhutada, Jadhav, Pinjari, Nemade, & Jain, ) and grape seed oil (Mohansrinivasan, Biswas, Naine S, Devi C., & Deori, ) studies. Therefore, it could be confirmed that the extracted product in this study was hazelnut oil.…”
Section: Resultssupporting
confidence: 77%
“…Si–O stretching bend of methylene group (–CH 2 ) was also observed at peak 721.93 cm ‒1 . The spectra pattern was similar with Moringaceae seed oil (Bhutada, Jadhav, Pinjari, Nemade, & Jain, ) and grape seed oil (Mohansrinivasan, Biswas, Naine S, Devi C., & Deori, ) studies. Therefore, it could be confirmed that the extracted product in this study was hazelnut oil.…”
Section: Resultssupporting
confidence: 77%
“…Other researchers established that grape seed extract containing about 89% of proanthocyanins, was also more active in the HCT116 cell line (30 µg/mL of extract killed about 60% of cells already after 48 h) [ 53 ]. Interestingly, grape seed extract showed lower activity against melanoma cancer cell line A431 (cell viability was reduced by only ~20% at 50 and 100 µg/mL concentrations, while in our experiment L4 and F4 fractions reduced melanoma IGR-39 cell viability by 50% at 50–100 µg/mL concentrations after 72 h of incubation [ 54 ]. It could be explained by the proanthocyanidins specificity in different cell lines and time and dose-dependent effect.…”
Section: Discussionmentioning
confidence: 91%
“…Grape seeds were also studied by FTIR spectroscopy. Ismail et al [31] used FTIR to study and quantify bioactive compounds in grape seeds. They identified carboxylate groups from gallic acid and proanthocyanidin gallate in the aqueous seed extract.…”
Section: Introductionmentioning
confidence: 99%